"Foi o trabalho que apareceu”: experiências de jovens mulheres na limpeza escolar - Libâneo, Flávia Sabina (2024)
This research aims to describe and analyze the experiences of young women inserted in the Young Apprentice Program, who work in the municipal schools of Sorocaba/SP in cleaning functions. Considering the educational and work character present in this labor insertion program, the specificities, difficulties and easiness found in this first job experience were observed. The Young Apprentice Program is aimed at young people from 14 to 24 years old, however, for the cleaning assistant course, the minimum age is 18 years. Thus, the young women participating in this research are in the age group between 18 and 24 years. Considering the scarce academic production found in bibliographic research on cleaning professionals in education, in addition to the lack of knowledge of other education professionals about these young women inserted in school, this research is necessary. Given its qualitative nature, a bibliographic survey was carried out, in addition to the application of 21 sociodemographic forms for profile survey and in-depth interviews with 06 young people for a better understanding of their experiences and trajectories. The interviews were conducted in two stages: the first during the first half of 2023, in person or remotely, according to the availability of the young women, and the second in January 2024, for further study. The theoretical framework is centered on the following authors: Maria Carla Corrochano, François Dubet, Helena Hirata and Patricia Hill Collins. Among the main results obtained, the idea of “a work that was available” and not chosen stands out; the use of this experience as a way to achieve better positions in the labor market; the need to consider non-teaching workers in schools as educators and the markers of gender, age, race and social class, corroborating with research that indicates that poor and racialized women are the majority in domestic work.